2018 Information Theory and Applications Workshop (ITA) 2018
DOI: 10.1109/ita.2018.8503191
|View full text |Cite
|
Sign up to set email alerts
|

Oversampled Adaptive Sensing

Abstract: We develop a Bayesian framework for sensing which adapts the sensing time and/or basis functions to the instantaneous sensing quality measured in terms of the expected posterior mean-squared error. For sparse Gaussian sources a significant reduction in average sensing time and/or mean-squared error is achieved in comparison to nonadaptive sensing. For compression ratio 3, a sparse 10% Gaussian source and equal average sensing times, the proposed method gains about 2 dB over the performance bound of optimum com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Note that in our simplified framework, A m+1 is restricted to be chosen from O F . We hence employ the worstcase adaptation strategy proposed in [1] and utilized in [2]: In subframe m, the adaptation function finds the permutation…”
Section: Posterior Information and Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that in our simplified framework, A m+1 is restricted to be chosen from O F . We hence employ the worstcase adaptation strategy proposed in [1] and utilized in [2]: In subframe m, the adaptation function finds the permutation…”
Section: Posterior Information and Adaptationmentioning
confidence: 99%
“…The sensing matrix in each subframe is adapted based on some posterior information determined from the measurements of previous subframes. In [1], it has been demonstrated that OAS achieves a considerable performance gain, when some prior information on the signal is available. The most well-known form of such prior information is sparsity which was explicitly studied in [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…T m , and hence increases the noise power in each individual sensing. Investigations have demonstrated that while this belief is true for signals with absolutely continuous priors, sequential adaptation is in fact beneficial when the signal has a mixture prior; see discussions in [1] and [11]. This is illustrative by considering an example from sparse recovery.…”
Section: A Sequential Sensing Via Oasmentioning
confidence: 96%
“…The initial study on OAS in [1] considered scenarios with orthogonal and deterministic projections. Such an assumption was primarily taken for sake of analytical tractability.…”
Section: B Contributionsmentioning
confidence: 99%
See 1 more Smart Citation